Aldehyde-functional thermoresponsive diblock copolymer worm gels exhibit strong mucoadhesion. Issue 23 (26th May 2022) - Brotherton, Emma E.; Neal, Thomas J.; Kaldybekov, Daulet B.; Smallridge, Mark J.; Khutoryanskiy, Vitaliy V.; Armes, Steven P.
Abstract : Optimizing the aldehyde content of thermoresponsive diblock copolymer worm gels via periodate oxidation leads to mucoadhesion performance comparable to that of chitosan (a gold standard positive control) in a fluorescence assay using porcine mucosa. Abstract : A series of thermoresponsive diblock copolymer worm gels is prepared via reversible addition–fragmentation chain transfer (RAFT) aqueous dispersion polymerization of 2-hydroxypropyl methacrylate using a water-soluble methacrylic precursor bearing pendent cis -diol groups. Selective oxidation using an aqueous solution of sodium periodate affords the corresponding aldehyde-functional worm gels. The aldehyde groups are located within the steric stabilizer chains and the aldehyde content can be adjusted by varying the periodate/ cis -diol molar ratio. These aldehyde-functional worm gels are evaluated in terms of their mucoadhesion performance with the aid of a fluorescence microscopy-based assay. Using porcine urinary bladder mucosa as a model substrate, we demonstrate that these worm gels offer a comparable degree of mucoadhesion to that afforded by chitosan, which is widely regarded to be a 'gold standard' positive control in this context. The optimum degree of aldehyde functionality is approximately 30%: lower degrees of functionalization lead to weaker mucoadhesion, whereas higher values compromise the desirable thermoresponsive behavior of these worm gels.